Preliminary evidence of safety and effectiveness of Loxoprofen Sodium Cataplasm combined with physiotherapy for myofascial pain syndrome treatment: A randomized controlled pilot clinical trial - Zhou, Xuewen; Li, Xuelian; Wang, Ziyang; Huang, Dong (Frontiers in Neurology, 2022)
Background: Myofascial pain syndrome (MPS) is one of the most common causes of chronic skeletal muscle pain, which is closely related to skeletal muscle myofascial trigger point (MTRP). Since there is no first-line treatment for Myofascial pain syndrome, we investigated loxoprofen sodium cataplasm combined with physiotherapy as a noninvasive therapy in patients at different levels, to a protocol with superior efficacy that is safe and easy to promote. Moreover, this treatment could represent an alternative therapeutic strategy for low-income patients to a Safer, more convenient and more economical treatment scheme. Methods: A randomized clinical study was aimed at evaluating the safety and efficacy of loxoprofen sodium cataplasm combined with physiotherapy in patients diagnosed with MPS in the pain clinic. We screened 100 MPS patients, and using a computer-generated random allocation sequence, we stratified patients in a 2:1:1:1 ratio (A: B: C: D) to one of four treatment groups: Group A received Loxoprofen Sodium Cataplasm combined with Extracorporeal shock wave therapy (ESWT)and Transcutaneous Electrical Nerve Stimulation (TENS). Group B received Loxoprofen Sodium Cataplasm alone. Group C received physiotherapy alone. Group D received Flurbiprofen Cataplasm combined with physiotherapy. After two weeks of treatment, the overall efficiency and secondary assessment indicators, including VAS scores, chronic soft tissue injury scores, ODI scores or NPQ scores, were evaluated before and after treatment to analyze the difference in efficacy of each group. Results: All Group were well tolerated with no reported adverse events. Significant treatment differences in the change from baseline in Total effective rate (primary efficacy endpoint) (P = 0.0078) were observed in subjects of Group A and Group C subjects. Conclusions: Loxoprofen Sodium Cataplasm combined with physiotherapy is superior in the treatment of MPS. Conclusion: Showing valuable data of efficacy in primary and secondary endpoints, Loxoprofen Sodium Cataplasm combined with physiotherapy is superior in the treatment of MPS. Trial registration number: ChiCTR2100054756 Retrospectively registered 26/12/2021